Existence of God: Antithetical Themes in “Dr. Faustus” and “Waiting for Godot” - Iftikhar Yousaf, Muhammad; Muhammad Nubli, Abdul Wahab; Nor Ashikin, Abdul Aziz; Iqbal, Muhammad (2016)
This paper is about the antithetical themes regarding the existence of God in two plays “Doctor Faustus” by Christopher Marlow and “Waiting for Godot” by Samuel Backett. Both the plays represent two different ages and religious orientations. The former is a tragedy of a doctor of philosophy who pledges his soul with the Devil for the sake of attaining the power of necromancy in a flagrant disregard to God’s commandments and is damned to hellfire whereas the latter is tragicomedy that projects meaninglessness of life through characters questioning the very significance of God’s existence. Hence it is presumed that heterogeneous themes running parallel to each other might arouse different emotions in the reader. In order to examine whether such opposing themes in two different dramas exist or not, textual excerpts were analyzed, literature was reviewed, critics views were collected, and opinion of the experts in teaching literature were gathered. Finally, it is concluded that both the plays do have themes which run into opposite directions regarding the existence of God leading to the arousal of unlike emotions.